Regional Fat Distributions Are Associated With Subclinical Right Ventricular Dysfunction in Adults With Uncomplicated Obesity - Liu, Jing; Li, Jing; Yu, Jianqun; Xia, Chunchao; Pu, Huaxia; He, Wenzhang; Li, Xue; Zhou, Xiaoyue; Tong, Nanwei; Peng, Liqing (Frontiers in Cardiovascular Medicine, 2022)
Objective: Obesity is a prominent public health problem that has increased cardiovascular mortality risks. However, the specific effects of obesity, independent of comorbidities, on cardiac structure and function has not been well clarified, especially those effects on the right ventricle (RV). Cardiovascular magnetic resonance (CMR) tissue tracking can assess detailed RV mechanical features. This study aimed to evaluate RV strain using CMR and assess its association with fat distributions in uncomplicated obese adults. Methods: A total of 49 obese patients and 30 healthy controls were included. The RV global function and strain parameters were assessed based on CMR. Body fat distributions were measured with dual X-ray absorptiometry. RV functional indices of obese patients were compared with those of healthy controls. Correlations among related body fat distribution parameters and RV function indices were conducted with multivariable linear regression. Results: Compared with healthy controls, the obese group had impaired RV strain with lower global longitudinal peak strain (PS), longitudinal peak systolic strain rate (PSSR), circumferential and longitudinal peak diastolic strain rates (PDSR) (all P < 0.05), while LV and RV ejection fractions were not significantly different between the two groups (P > 0.05). Multivariable linear regression analysis demonstrated that android fat% was independently associated with longitudinal PS (β = -0.468, model R2 = 0.219), longitudinal PDSR (β = -0.487, model R2 = 0.237), and circumferential PSSR (β = -0.293, model R2 = 0.086). Trunk fat% was independently associated with longitudinal PSSR (β = -0.457, model R2 = 0.209). In addition, the strongest correlations of circumferential PDSR were BMI and gynoid fat% (β = − 0.278, β = 0.369, model R2 = 0.324). Conclusions: Extensive subclinical RV dysfunction were found in uncomplicated obese adults. BMI, as an index of overall obesity, was independently associated with subclinical RV dysfunction. In addition, central obesity (android fat and trunk fat distributions) had a negative effect on subclinical RV dysfunction, while peripheral obesity (gynoid fat distribution) had a positive effect on it.